Genomewide Elucidation of Drug Resistance Mechanisms for Systemically Used Antifungal Drugs Amphotericin B, Caspofungin, and Voriconazole in the Budding Yeast - Balkan, Cigdem; Ercan, Ilkcan; Isik, Esin; Sahin Akdeniz, Esra; Balcioglu, Orhan; Kodedová, Marie; Zimmermannová, Olga; Dundar, Muhammed; Sychrová, Hana; Koc, Ahmet (Antimicrobial agents and chemotherapy, 2019)
There are only a few antifungal drugs used systemically in treatment, and invasive fungal infections that are resistant to these drugs are an emerging problem in health care. In this study, we performed a high-copy-number genomic DNA (gDNA) library screening to find and characterize genes that reduce susceptibility to amphotericin B, caspofungin, and voriconazole in Saccharomyces cerevisiae We identified the PDR16 and PMP3 genes for amphotericin B, the RMD9 and SWH1 genes for caspofungin, and the MRS3 and TRI1 genes for voriconazole. The deletion mutants for PDR16 and PMP3 were drug susceptible, but the other mutants had no apparent susceptibility. Quantitative-PCR analyses suggested that the corresponding drugs upregulated expression of the PDR16, PMP3, SWH1, and MRS3 genes. To further characterize these genes, we also profiled the global expression patterns of the cells after treatment with the antifungals and determined the genes and paths that were up- or downregulated. We also cloned Candida albicans homologs of the PDR16, PMP3, MRS3, and TRI1 genes and expressed them in S. cerevisiae Heterologous expression of Candida homologs also provided reduced drug susceptibility to the budding yeast cells. Our analyses suggest the involvement of new genes in antifungal drug resistance.
Keywords: Drug Resistance, Fungal; antifungální látky; genomics; Amphotericin B; Candida albicans; vorikonazol; drug resistance; kaspofungin; Saccharomyces cerevisiae Proteins; voriconazole; amfotericin B; fungální léková rezistence; amphotericin B; Microbial Sensitivity Tests; antifungal agents; Antifungal Agents; Caspofungin; Voriconazole; multidrug resistance; Saccharomyces cerevisiae; mikrobiální testy citlivosti; caspofungin; Saccharomyces cerevisiae - proteiny; Saccharomycetales